Severity of hyperechoic pancreas on ultrasonography as a risk factor for glycemic progression - Oh, Jiyun; Park, Hyun Jeong; Lee, Eun Sun; Park, Sung Bin; Choi, Byung Ihn; Ahn, Soohyun (Ultrasonography, 2021)
Purpose: The aim of this study was to evaluate the association between the severity of hyperechoic pancreas (HP) on ultrasonography (US) and glycemic progression. Methods: In total, 1,386 participants who underwent abdominal US as part of health examinations between December 2008 and May 2014 were included in this retrospective study. We classified pancreatic echogenicity on a 4-point scale, and compared it using two distinct criteria: fatty pancreas (FP) 1 criterion (normal vs. ≥mild HP) and FP2 criterion (normal/mild HP vs. ≥moderate HP). According to the presence of nonalcoholic fatty liver disease (NAFLD), participants were subdivided into four groups: non-NAFLD and non-HP, isolated NAFLD, isolated HP, and HP with NAFLD. Glycemic progression was defined as progression from normoglycemia to prediabetes or diabetes or progression from prediabetes to diabetes. Results: During the follow-up (median, 5.9 years), 262 of the 1,386 participants developed glycemic progression. Using FP2, the probability of glycemic progression across the four subgroups showed cumulative aggravation for NAFLD and HP (all P<0.05). Isolated HP showed a higher probability of glycemic progression than isolated NAFLD according to FP2 (P<0.001). The highest probability of glycemic progression was observed in patients with both NAFLD and HP (P<0.001). The hazard ratio for glycemic progression increased with the severity of HP. Conclusion: Increasing severity of HP on US was found to be significantly correlated with glycemic progression. Moreover, isolated HP of moderate or greater severity predicted glycemic progression independent of NAFLD.
Keywords: Diabetes; Fatty pancreas; Hyperechoic pancreas; Nonalcoholic fatty liver disease; Ultrasonography